An immunocytochemical study of several types of gut endocrine cells in chick embryos - Alison, Barbara Clare (My University, 2014)
The time of first appearance and distribution of several types of peptide-sto*. ing cells were studied in the gastrointestinal tract of chick embryos between 12 days of incubation ana hatching. Immunocytochemical methods have been employed to demonstrate cells immunoreactive for gastrin/cholecystokinin (CCK), neurotensin, somatostatin, glucagon and avian pancreatic polypeptide (APP) in the p.oventriculus, gizzard, pyloric region, duodenum, upper and lower ileum, caecum and rectum. No immunoreactive cells were found in any region at 11 days of incubation. Immunoreactive cells which first appeared at 12 days were: somatostatinand neurotensin-immunoreactivc cells in the y proventr Lculus, pyloric vs ion and duolenum, neurotensin-immunoreactive cells in the rectum? at 13 days, APP-immunoreact ive cells in the duodenum and aiy->r ileuM, glucagon-immunoreact ive cells in the proventriculus: at 14 d a y s , somatostatin- and neurotensin-immunoreact ive cells in the upper and lower ileum, gastrin/CCK-immunoreactive cells in the small intestine, APP-immunoreact ive cells in the proventriculus and lower ileum, glucagon-irmunor eacc ive cells in the pyloric region and small intastine: at 16 days, gastrin/CCK-immunoreactive cells in the pyloric region. Subjective assessment showed an increase in frequency of all five cell types until the numbers at hatching were approximated, a few days before hatching. No immunoreactive cells of any type were detected in the gizzard; only neurotensin-immunoreact ive cells were detected in the caecum and rectum. When these endocrine cells first appeared, the surface epithelium of the gastrointestinal tract was relatively undifferentiated. Cells of all five types were found in glands once morphogenesis h d begun. The coexistence of APP- and glucagon-1 ike immunoreaetivity in the same cells was studied in the proventriculus and small intestine, and of g a s t r m / C C K - and neurotens in-like immunoreact ivity in the pyloric region and duodenum. Consecutive sections of each region were examined at 17$-, 19- and 7 1-days of incubation. For practical reasons, earlier stages, when cell numbers were small, were not studied. However, the trend shown in the proventriculus and ileum suggests that most, if not all, the relevant cells may contain APP- and glucagon-like peptides from the time they first appear. No dual immunoreactivity was detected in the duodenum. The proportion of cells demonstrating dual immunoreactivity for gastrin/CCK and neurotensin showed no clear change in either region.